2014
DOI: 10.1371/journal.pone.0097663
|View full text |Cite
|
Sign up to set email alerts
|

The Budding Yeast Amphiphysin Complex Is Required for Contractile Actin Ring (CAR) Assembly and Post-Contraction GEF-Independent Accumulation of Rho1-GTP

Abstract: The late events of the budding yeast cell division cycle, cytokinesis and cell separation, require the assembly of a contractile actomyosin ring (CAR), primary and secondary septum formation followed by enzymatic degradation of the primary septum. Here we present evidence that demonstrates a role for the budding yeast amphiphysin complex, a heterodimer comprising Rvs167 and Rvs161, in CAR assembly and cell separation. The iqg1-1 allele is synthetically lethal with both rvs167 and rvs161 null mutations. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Amph-dependent Rho1 and Dia recruitment at the membrane folded around the spermatid heads triggers actin polymerization We found that the N-BAR family protein Amph recruits Rho1 and Dia on the somatic cell membrane during the final stages of spermatid maturation and promotes F-actin assembly at the basket. Rvs 167, the Amph ortholog in yeast, is also suggested to promote Rho1 localization at the membrane furrow during cytokinesis (Cundell and Price, 2014). Some BAR-domain proteins are shown to interact with the Cdc42 and Rac1 families of Rho-GTPases through their SH3 domain and nucleate F-actin assembly through the WASp/WAVE NPFs (Aspenströ m, 2014;Fricke et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Amph-dependent Rho1 and Dia recruitment at the membrane folded around the spermatid heads triggers actin polymerization We found that the N-BAR family protein Amph recruits Rho1 and Dia on the somatic cell membrane during the final stages of spermatid maturation and promotes F-actin assembly at the basket. Rvs 167, the Amph ortholog in yeast, is also suggested to promote Rho1 localization at the membrane furrow during cytokinesis (Cundell and Price, 2014). Some BAR-domain proteins are shown to interact with the Cdc42 and Rac1 families of Rho-GTPases through their SH3 domain and nucleate F-actin assembly through the WASp/WAVE NPFs (Aspenströ m, 2014;Fricke et al, 2009).…”
Section: Discussionmentioning
confidence: 99%